O ensino de história na escola normal de São Paulo (1880-1890) - Martins, Ritchie Soares Barbosa (2013)
The objective of this research is to study the teaching of history at the Normal School of Sao Paulo from 1880 to 1890 to see if that school, facing teacher training for schools first letters had their bases connected to what was proposed in the programs of elementary schools or secondary school. The proposed analysis begins at the time the school went through its third founding in 1880 until 1890, the year it happened a reform school for suitability to the republican model. The research is founded on the contributions of the "History of School Subjects" and uses the theoretical framework of authors such as André Chervel, Ivor Goodson, seeking a search that is not restricted to teaching and pedagogical issues, but also, the significance of this knowledge the training of teachers in a school that was now being consolidated in the educational history of São Paulo, trying to understand the teaching of history from its objectives, content, teaching methods proposed and production, in a historical perspective